Nutrition Risk Screening 2002 for adult cancer patients: a systematic review and meta-analysis - Pengpeng, Wang; Yanmei, Tan; Kim, Lam Soh; Kim, Geok Soh; Chuanyi, Ning; Li, Xue; Yunhong, Lu; Jie, Yang (Taylor and Francis, 2024)
It is critical to screen and assess malnutrition in cancer patients early. However, there is no uniform standard for nutritional risk screening and malnutrition assessment. We aimed to analyze the effects of the Nutrition Risk Screening 2002 (NRS2002) in screening for nutritional risk among adult cancer patients, using the Patient-Generated Subjective Global Assessment (PG-SGA) as the reference standard. A systematic search was performed using PubMed, Embase, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, and China Science and Technology Journal Database (VIP). Studies comparing NRS2002 with PG-SGA in adult cancer patients were included. To assess the quality of the included studies, the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) was used. The combined sensitivity, specificity, diagnostic odds ratio (DOR), and the area under the receiver-operating characteristic curve (AUC) were calculated. In addition, sensitivity, subgroup, and publication bias analyses were performed. Thirteen articles involving 3,373 participants were included. The combined sensitivity, specificity, DOR, and AUC were 0.62 (95% CI, 0.60–0.64), 0.86 (95% CI, 0.84–0.88), 11.23 (95% CI, 8.26–15.27), and 0.85 (95% CI, 0.82–0.88), respectively. For adult cancer patients, NRS2002 has moderate sensitivity, high specificity, and high AUC in screening for nutritional risk.